PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 1 TIMPEH - Jenurti, Resnita (Jurnal Edukasi dan Penelitian Matematika, 2025)
A strong understanding of mathematical problem-solving skills is essential for critical thinking when faced with problems in a variety of real-life situations. However, the lack of student engagement in learning makes this ability still relatively low, especially in the seventh grade of SMPN Timpeh. We used the Problem Based Learning (PBL) paradigm to overcome this obstacle. The purpose of this study was to determine whether students' performance in mathematical problem-solving tasks improved when exposed to the PBL model compared to a more traditional learning model. This study used a descriptive quasi-experimental design with a posttest-only control group. The null hypothesis (H0) was rejected as the P-Value achieved, with α = 0.05, was 0.017, indicating that the P-Value was smaller than α. Based on these findings, the use of PBL model successfully provided optimal results in problem solving compared to conventional learning.Keywords– Mathematical Problem Solving Ability, Problem Based Learning, Conventional Learning